(untitled) (World Economics and Finance Bulletin, 2025)
The main goal of this study was to examine how digital currencies influence the global financial system. It focused on their effects on financial stability and monetary policies. The research aimed to better understand this topic and explore what the future might hold. A descriptive analytical method was used to review the key ideas about digital currencies in finance. The study then looked at how these currencies affect stability and policy decisions. It found that central banks follow very strict monetary policies. At the same time, many countries are adopting digital currencies. The participants in the research consider the financial system to be fairly stable. According to these results, the research suggests establishing an appropriate economic setting for digital currencies. This is essential for their smooth and effective use in the Iraqi economy